Risk factors of multidrug resistant tuberculosis among patients with tuberculosis at selected multidrug resistance treatment initiative centres in southern Ethiopia: a case-control study - Fantahun Admassu; Ermias Abera; Addisalem Gizachew; Tagesse Sedoro; Taye Gari (BMJ Open)
Objective To identify the risk factors for multidrug resistant tuberculosis (MDR-TB) among patients with TB at selected MDR-TB treatment initiative centres, southern Ethiopia, 2021.Design An unmatched case-control study was employed.Setting Multidrug resistance treatment initiative centres in southern Ethiopia (Nigist Elen Mohamed Memorial Comprehensive Specialized Hospital and Butajira General Hospital).Participants A total sample size of 392 (79 cases and 313 controls) were selected by the systematic sampling technique. Cases were all patients with TB with culture proven or line probe assay confirmed Mycobacterium tuberculosis resistant to at least both isoniazid and rifampicin and registered on second-line TB treatment. Controls were all patients with bacteriological (molecular) proven drug-susceptible TB strains and whose recent smear results were turned to negative and registered as cured. Both bivariate and multivariable logistic regression analysis was used to identify risk factors of MDR-TB infections.Main outcome measure Identifying the risk factors for MDR-TB.Results A total of 392 participants (79 cases and 313 controls) were interviewed. Multivariable analysis showed that direct contact with known patients with TB (AOR =4.35; 95% CI: 1.45 to 9.81), history of previous TB treatment (AOR=2.51; 95% CI: 1.50 to 8.24), history of cigarette smoking (AOR=3.24; 95% CI :2.17 to 6.91) and living in rural area (AOR=4.71; 95% CI :3.13 to 9.58) were identified risk factors for MDR-TB infections.Conclusions The study findings revealed that direct contact with known patients with TB, previous history of TB treatment, history of cigarette smoking and rural residence were potential risk factors for the occurrence of MDR-TB. In order to reduce the burden of drug resistance, strategies of controlling MDR-TB in the study area should emphasise on enhancing public health education and reducing treatment interruptions of patients with TB and drug-resistant TB.